Seasonal controls on sediment transport and deposition in Lake Ohau, South Island, New Zealand: Implications for a high‐resolution Holocene palaeoclimate reconstruction. Issue 3 (8th December 2014) - Roop, Heidi A.; Dunbar, Gavin B.; Levy, Richard; Vandergoes, Marcus J.; Forrest, Alexander L.; Walker, Sharon L.; Purdie, Jennifer; Upton, Phaedra; Whinney, James
Abstract Laminated sediments in Lake Ohau, Mackenzie Basin, New Zealand, offer a potential high‐resolution climate record for the past 17 kyr. Such records are particularly important due to the relative paucity of detailed palaeoclimate data from the Southern Hemisphere mid‐latitudes. This paper presents outcomes of a study of the sedimentation processes of this temperate lake setting. Hydrometeorological, limnological and sedimentological data were collected over a 14 month period between 2011 and 2013. These data indicate that seasonality in the hydrometeorological system in combination with internal lake dynamics drives a distinct seasonal pattern of sediment dispersal and deposition on a basin‐wide scale. Sedimentary layers that accumulate proximal to the lake inflow at the northern end of the lake form in response to discrete inflow events throughout the year and display an event stratigraphy. In contrast, seasonal change in the lake system controls accumulation of light (winter) and dark (summer) laminations at the distal end of the lake, resulting in the preservation of varves. This study documents the key processes influencing sediment deposition throughout Lake Ohau and provides fundamental data for generating a high‐resolution palaeoclimate record from this temperate lake.